Aplicabilidade da Lei de Acesso à Informação: uma análise das informações disponibilizadas nos websites institucionais das universidades públicas estaduais e municipais brasileiras - Araújo, Rafael Melo Gomes de (2019)
This research proposes to perform a critical analysis on the requirements that the Law of Access to Information (LAI) (Law 12.527 / 2011) establishes for websites in public institutions with emphasis on Brazilian state and municipal public universities. The general objective of this research is to analyze the disposition of the information required by the LAI in the institutional electronic portals of the State and Municipal Public Universities, evaluating their conformity to what is required by law, with special emphasis on their transparency portals. For data collection, we opted for documentary research, considering the value of a site as a document that can be analyzed. For this, we used two methods: the comparative method, in which the analysis of all the institutional electronic sites was done and how they disposed the information characterized as obligatory by the Law of Access to Information; and the indicia method, used to verify innovative actions, good practices and barriers in transparency portals of the researched institutions. Finally, it was possible to analyze the degree of transparency of the Brazilian State and Municipal Public investigated universities for the information made available in their institutional websites. In conclusion, it was evidenced that universities urgently need to conform to the minimum requirements of LAI, in order to facilitate access to information, promoting democracy through participation and social control.